Beyond the Negotiation between Tradition and Innovation in the Continuity of Art: Merleau-Ponty’s Phenomenology of the Body in Balinese Wayang Tantri - Dwipayana, A. A. Putra; Syamsuddin, Mukhtasar; Ariani, Iva (Jurnal Penelitian Agama Hindu, 2026)
Studies of Balinese art have often approached artistic continuity through a dichotomy between tradition and innovation an approach that often neglects the existential dimension of artistic creation. In studies of Wayang Tantri in particular, this framework has likewise been used to interpret creativity as the outcome of negotiation between tradition and innovation. However, the principle of kawi dalang fundamentally unsettles this view, as it presupposes difference and novelty as inherent conditions of the dalang’s (puppeteer) creative practice. This article proposes an alternative perspective that moves beyond such dichotomous assumptions by approaching Wayang Tantri as a mode of artistic existence in which meaning emerges from the dalang’s embodied experience rather than from a static opposition between traditional forms and creative novelty that marginalizes the subject. The study adopts a qualitative philosophical methodology, drawing on Merleau-Ponty’s phenomenology to examine creativity in Wayang Tantri. The findings show that, when situated within an existential dimension, creativity entails an understanding of art and the body as inseparable. Artistic expression unfolds through the historical situatedness of the dalang’s body within a continuously enacted relationship with the world, which constitutes the field in which artistic meaning is disclosed. These findings challenge the dichotomous tradition innovation framework, including the notion of “negotiation,” which implicitly reifies art as a mere object of observation. Accordingly, Wayang Tantri is understood as a living, dynamic, and relational artistic phenomenon, in which existential experience provides an epistemological foundation for understanding Balinese art and serves as a source of truth in artistic practice.